Lady and the champ: the shared career experiences and retirement transition of a champion jockey and his partner - Reddington, E.; Winter, S. (Psychology of Sport and Exercise, 2025)
Elite sporting careers are made up of a succession of transitions and adjustments across multiple layers. Part of the microenvironment is an athlete's romantic partner who moves through the transitions alongside them, being impacted along the way. Though researchers are yet to explore jockeys and their partners experiences within the horse racing context. Framed through the transition environment working model (Henriksen et al., 2024) and supported by the family systems theory (Broderick, 1993), this study aimed to explore the career experiences and retirement transition of a retired Champion jockey as perceived by him and his female partner. Using interpretative phenomenological analysis, four semi-structured interviews were conducted with the two participants, Richard and Lizzie Hughes (M age = 46.5, SD = 2.1) who consented to their identities being disclosed. Three themes were constructed: "It was all worth it"; "You can't have the good times without the bad"; and "It's been a journey but one I clearly wouldn't change". Findings of this study highlighted the influence of the micro-level environment in shaping transition experiences, which ultimately impacted the partner too. Secondly, addiction and obsessive passion were found throughout transition experiences. Thirdly, despite being normative the retirement transition process presented emotional and physical challenges across jockey and partner. In all, the study provided a novel insight of the experiences and perceptions of both jockey and partner. Further research attention and applied support avenues for both parties are warranted, since their experiences are closely intertwined.